Mobile genetic elements drive the multidrug resistance and spread of Salmonella serotypes along a poultry meat production line - Krüger, Gabriel I.; Pardo-Esté, Coral; Zepeda, Phillippi; Olivares-Pacheco, Jorge; Galleguillos, Nicolas; Suarez, Marcia; Castro-Severyn, Juan; Alvarez-Thon, Luis; Tello, Mario; Valdes, Jorge H.; Saavedra, Claudia P. (Frontiers in Microbiology, 2023)
The presence of mobile genetic elements in Salmonella isolated from a chicken farm constitute a potential risk for the appearance of emerging bacteria present in the food industry. These elements contribute to increased pathogenicity and antimicrobial resistance through genes that are related to the formation of biofilms and resistance genes contained in plasmids, integrons and transposons. One hundred and thirty-three Salmonella isolates from different stages of the production line, such as feed manufacturing, hatchery, broiler farm, poultry farm and slaughterhouse, were identified, serotyped and sequenced. The most predominant serotype was Salmonella Infantis. Phylogenetic analyses demonstrated that the diversity and spread of strains in the pipeline are serotype-independent, and that isolates belonging to the same serotype are very closely related genetically. On the other hand, Salmonella Infantis isolates carried the pESI IncFIB plasmid harboring a wide variety of resistance genes, all linked to mobile genetic elements, and among carriers of these plasmids the antibiograms showed differences in resistance profiles and this linked to a variety in plasmid structure, similarly observed in the diversity of Salmonella Heidelberg isolates carrying the IncI1-Iα plasmid. Mobile genetic elements encoding resistance and virulence genes also contributed to the differences in gene content. Antibiotic resistance genotypes were matched closely by the resistance phenotypes, with high frequency of tetracycline, aminoglycosides and cephalosporins resistance. In conclusion, the contamination in the poultry industry is described throughout the entire production line, with mobile genetic elements leading to multi-drug resistant bacteria, thus promoting survival when challenged with various antimicrobial compounds.